Facilitating Second Language Acquisition : An analysis of English language teaching materials in Finland - Valanne, Roosa (My University, 2025)
The purpose of this study was to investigate the potential of Finnish teaching materials of the English language to facilitate language acquisition according to language learning research. Seven student workbooks from two book series were analysed using an established framework for materials analysis and evaluation. The results showed that only one language acquisition principle, focusing on meaning, was well represented in the analysed sample, while several others were scarcely found in any of the materials. The findings imply that coursebooks should not be used as the only source of input and tasks for language learners, and that teachers should utilize other authentic sources of input to ensure proper communicative competence and language acquisition for their learners.
Keywords: Second language acquisition, foreign language teaching, teaching materials